Electronic structures of isoquercitrin and its pharmacokinetic exploration with Dengue virus 1 NS5 methyl transferase: Isoquercitrin interaction with Dengue NS5-MTase - Alwabli, Afaf S (Cellular and Molecular Biology, 2025)
An enzyme called dengue virus (DENV) non-structural protein 5 (NS5) methyltransferase (MTase) aids in the virus’s replication by encasing viral RNA. Here, we report on the impact of the dengue virus (DENV) protein NS5 methyltransferase domain (NS5-MTase). This study investigates the structural, electronic, and biological properties of isoquercitrin using Density Functional Theory (DFT). Frontier molecular orbital energies were evaluated to assess the reactivity of the compounds, while molecular electrostatic potential mapping provided insights into charge distribution. In-silico ADME and toxicity analyses were conducted to determine the drug-likeness and safety profiles of the compound. Molecular docking simulations examined the binding interactions between Isoquercitrin and its target protein. To evaluate the potential of Isoquercitrin as a drug candidate, aspects such as absorption, distribution, metabolism, excretion, toxicity (ADMET), drug-likeness, and compound accessibility were analyzed. The ADME and toxicity results revealed promising drug-like properties and low toxicity, underscoring the compound’s therapeutic potential.